The Effect of Religious Culture Implementation on Students’ Moral Values at MTs Islamiyah Tanjung Raja, North Lampung - Putri Maharani Pratiwi; Dwi Noviatul Zahra (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This research was conducted to determine whether the application of religious culture has an effect on the moral values of students at MTs Islamiyah Tanjung Raja Lampung Utara. This study is an ex post facto study using quantitative research methods. The research data was obtained using questionnaires, observations, and documentation. The sample in this study consisted of 30 students obtained through simple random sampling. The data analysis technique used in this study was simple regression testing. The results showed that there was a significant effect of the application of religious culture on the moral values of students at MTs Islamiyah Tanjung Raja Lampung Utara. This is evidenced by the results of the simple regression test, namely the result of Fcount of 14.098 and the result of Ftable of 4.196, which means that Fcount > Ftable or 14.098 > 4.196. According to these calculation results, Ha is accepted and Ho is rejected, meaning that there is an influence of the application of religious culture on the moral values of students at MTs Islamiyah Tanjung Raja Lampung Utara